UUM Network Traffic Analysis and Users' Website Preferences - Al-Kawaz, Mustafa Mohammed Ibrahim (2012)
The current world is experiencing a revolution in Internet services and networking; a revolution that provided and continues to provide varying features and invaluable tools to computer networks. On the other hand, several problems are being faced by users and global organizations in networking including lack of bandwidth and packet loss during transmission which impacts Internet efficiency and the performance of network. These issues can be rectified through the measurement and analysis of the network’s performance. Moreover, for network performance enhancement, it is imperative to study users’ behaviour. Therefore, the main objectives of the present study are to identify UUM network performance through Internet traffic and to highlight users’ behaviour. A total of three methodological steps are carried out to meet the objectives of the study; the first one is the data collection phase whereby the source for data collection is taken from the presently used main distributed switch in an hour for each working day in a duration of one week; the second one is the data analysis phase where Wireshark is used to provide the statistics of traffic and finally; the third phase is the data presentation where Microsoft Excel is utilized to present data. Study findings presents valuable information of network bandwidth, data loss rates and Ethernet traffic distribution, in addition to the fact that is social websites are the most websites used in UUM. These findings leads to facilitate the enhancement of UUM network performance and Internet bandwidth strategies.